Doktrin kebebasan berkontrak dalam kontrak jualan barang : ketidaksesuaian sebagai doktrin landasan pembentukan undang-undang kontrak pengguna - Sakina Shaik Ahmad Yusoff (Fakulti Undang - Undang, 2000)

(untitled)
The 19th century saw the development of contract law based on the idea of freedom of contract. The influence of free market economy and laissez-faire contributed to the idea that individuals should be left free to make private arrangements. The 20th century saw great social and economic change, which heralded a swing away from the classic theory of freedom of contract. During this period it began to be realized that the notion of freedom of choice rested on many uncertain and fragile assumptions. In the realm of consumer sale of goods, there exists a fundamental inequality in terms of bargaining power, knowledge concerning the characteristics and technical components of the goods, and resources, between consumers and traders. Thus freedom of contract ceases to appropriate as the underlying doctrine for the formulation of laws regulating consumer sale contracts. This article is devoted to analyzing the doctrine of freedom of contract in the light of consumer contracts. The article also looks at some inroads upon the doctrine of freedom of contract and also explores some alternatives to the concept of freedom of contract as the underlying doctrine for consumer contract law